A Meta-Analysis of Relations Between Achievement and Self-Concept. (June 2020) - Möller, Jens; Zitzmann, Steffen; Helm, Friederike; Machts, Nils; Wolff, Fabian
According to the internal/external frame of reference model, academic achievement has a strong impact on people's self-concept, both within and between subjects. We conducted a series of meta-analyses of k = 505 data sets containing the six bivariate correlations between achievement and self-concept in two subjects. Negative paths from achievement to noncorresponding self-concept, indicating dimensional comparison effects, were strongest when the subjects were dissimilar with regard to the math-verbal continuum, reduced but still significantly negative when both subjects belonged to the verbal domain, and near-zero when both subjects belonged to the math/science domain. Additionally, we found stronger positive paths from achievements to corresponding self-concepts, indicating social comparison effects, and stronger dimensional comparison effects for grades than for standardized test scores, and for older rather than younger students. We extend dimensional comparison theory by discussing these results with particular regard to the nonexistence of assimilation effects, the effects of subject similarity on dimensional comparison effects, and other moderators of dimensional comparison effects.